2019
DOI: 10.32615/ps.2019.049
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical, physiological, and molecular analysis of a chlorophyll-deficient mutant in tree peony (Paeonia suffruticosa)

Abstract: Tree peony is a famous ornamental plant in the world. However, little is known about the leaf color mutants in tree peony. The present study monitored the physiological and photosynthetic properties of a yellow leaf mutant (yl1) in tree peony. The results showed that the yl1 mutant had lower pigment contents, but increased chlorophyll (Chl) a/b and carotenoids to Chl ratio. Microstructure and ultrastructure analysis showed that the yl1 mutant had smaller chloroplasts, few thylakoid stacks, and a few stroma thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Soluble sugar is one of the main storage substances of the energy metabolism in plants. In this study, the decrease of soluble sugar content in yl1 mutant might occur due to the decline of PSII and PSI functions and lower photosynthetic rate (Chang et al 2019). This study was consistent with that of rice (Oryza sativa) yellow-leaf mutant (Hu 2017) and yellow-leaf mutant rgm (1-20YY) in common wheat (Triticum aestivum) (Liu et al 2016a).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Soluble sugar is one of the main storage substances of the energy metabolism in plants. In this study, the decrease of soluble sugar content in yl1 mutant might occur due to the decline of PSII and PSI functions and lower photosynthetic rate (Chang et al 2019). This study was consistent with that of rice (Oryza sativa) yellow-leaf mutant (Hu 2017) and yellow-leaf mutant rgm (1-20YY) in common wheat (Triticum aestivum) (Liu et al 2016a).…”
Section: Discussionsupporting
confidence: 87%
“…The decrease of F0, Fm, F0', and Fm' in yl1 mutant showed a reduction of light energy capture efficiency and utilization in PSII reaction center. The lower values of Fv/ Fm, Fv'/Fm', ΦPSII, and ETR of yl1 mutant indicated that the light energy-utilization efficiency decreased in yl1 mutant (Xiao et al 2013, Yang et al 2014, which was consistent with the photosynthetic rate of yl1 mutant measured previously (Chang et al 2019). There was no significant difference in qP between yl1 mutant and WT, which might imply that the reduction of Chl content did not necessarily have a significant effect on photochemical quenching.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the yellowing of leaves is getting in the focus of current research. For example, Li et al [2] reported that lower chlorophyll and higher carotenoid content (especially lutein) are the main factors for yellowing of gingko leaves, and Chang et al [7] found that the ratio of Plants 2020, 9, 169 of 17 chlorophyll a/b and carotenoid to chlorophyll increased in the leaves of yellow leaf mutant (yl1) of tree peony.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the origin of albinism, most studies have shown that albino plants present not only the loss of chlorophyll, but also changes in plastid biogenesis (Caredda et al . 2004; Fambrini et al 2007; Wu et al 2014; Chang et al 2019). Chloroplasts are formed from proplastids during cell development and, in albino plants, these proplastids fail to differentiate into chloroplasts, leading to malformation of thylakoid membranes (Kumari et al 2009), the sites of photosystems and chlorophylls, as observed here in D. regia .…”
Section: Discussionmentioning
confidence: 99%